THE RELATIONSHIP BETWEEN UNIVERSITY STUDENTS’ ATTITUDES TOWARDS ICT AND MEDIA TOOLS IN LEARNING ENGLISH AND THEIR EMOTIONAL INTELLIGENCE - Z. Zuhal Güven (Selçuk İletişim)
This study aimed to investigate the relationship between the attitudes of university students towards using Information and Communication Technology (ICT) and media tools in learning English and their emotional intelligence. It also investigated whether the attitudes of university students towards using ICT and media tools in learning English and their emotional intelligence varied according to their gender and departments.  The Turkish adaption of the revised Schutte emotional scale and The Attitude Scale for the Use of Media and ICT in Learning English were used as instruments to collect data in the study, which involved 143 female and 84 male, in total 227, university students. The independent t test, one way analysis of variance and Pearson product moment correlation technique were used to analyze the data obtained related with the variables gender, departments and emotional intelligence respectively. A positive relationship between the attitudes of participants and emotional intelligence was found. The other finding was that the attitudes of university students towards ICT and media use in learning English varied significantly according to their gender and departments. It was recommended that more comprehensives studies be conducted with different and various working groups to develop new language programs from broader perspectives.  This study aimed to investigate the relationship between the attitudes of university students towards using Information and Communication Technology (ICT) and media tools in learning English and their emotional intelligence. It also investigated whether the attitudes of university students towards using ICT and media tools in learning English and their emotional intelligence varied according to their gender and departments.  The Turkish adaption of the revised Schutte emotional scale and The Attitude Scale for the Use of Media and ICT in Learning English were used as instruments to collect data in the study, which involved 143 female and 84 male, in total 227, university students. The independent t test, one way analysis of variance and Pearson product moment correlation technique were used to analyze the data obtained related with the variables gender, departments and emotional intelligence respectively. A positive relationship between the attitudes of participants and emotional intelligence was found. The other finding was that the attitudes of university students towards ICT and media use in learning English varied significantly according to their gender and departments. It was recommended that more comprehensives studies be conducted with different and various working groups to develop new language programs from broader perspectives.